Perbandingan Administrasi Publik Antara Swedia dan Indonesia - Nadia Hidayanti; Indra Wardhana; Hudly Gumilar; Sandry Sianipar; Dewi Mutiara Kartika (Centre for Public Policy and Management Studies, 2008)
This article discusses the comparison of ombudsman commissions in Sweden and Indonesia. In particular it explores the historical background, the legal basis and how ombudsman works in both countries. Furthermore, this article also discusses the importance of ombudsman as one of control mechanisms from the public regarding government's performance.Keywords: Ombudsman, Sweden, Indonesia